Malay Reservation Land: A Legal and Historical Analysis - Mobarak Ali, Bashiran Begum (2002)
The thesis is a study on the legal and historical aspect of Malay reservation land. It aims to examine the Malay reservation law found in the various states' Enactment, including the provisions of the Federal Constitution. Malay reservation land can be said to represent land within the boundary of a state, which at law can only be owned or transferred to Malay. This general concept embraces the Malay Holdings in Terengganu. In a more specific sense, a Malay reservation land is defined in Article 89 of the Federal Constitution. It was the British who introduced the Malay reservation land to protect the Malays. At present these laws that protect the Malay race have been abused. For example, acquired Malay reservation land has not been replaced immediately by the government as required by the provision of the Federal Constitution. Above all, the Malay reservation land is still within the ambit of a low market value, due to the fact of its location and lack of infrastructure. In addition, the Malay reservation law is rigid in its application, as it does not allow any dealing with non-Malays. This research attempts to justify why and how the Malay reservation institution was introduced. The study is a mix of descriptive and analytical approach. The data were gathered through library research from the higher institutions, Malaysian Archive and the land office. The major obstacles faced were on the collection of overseas statutes and the confidentiality on collection of land policies in the land office. The aim of the collection was to observe and analyse the development of the Malay reservation law in order to examine the obstacles that have caused the lack of development of Malay reservation land. In line with the findings outlined above, the research also attempts to suggest some recommendations towards improving the Malay reservation law and finally one uniform law on Malay reservation for the welfare and development of the Malays should be enacted.